Effectiveness and safety of acupoint application for chronic obstructive pulmonary disease: A protocol for updated systematic review and meta-analysis. Issue 18 (7th May 2021) - Zhang, Hao-Yang; Huang, Han; Pang, Li-Jian; Lv, Xiao-Dong; Zheng, Wei-Dong
Abstract: Background: Acute exacerbation is a primary cause of repeated hospitalization and death in chronic obstructive pulmonary disease (COPD) patients. Therefore, how to control the symptoms of COPD at stable stage and reduce the number of acute exacerbation is a hot spot of medical research. Acupoint application (AA) is a significant part of external treatment of traditional Chinese medicine (TCM), Previous researches have reported that AA can be applied to the treatment of COPD. Nevertheless, its effectiveness is still inconclusive. This systematic review (SR) and meta-analysis is designed to appraise its effectiveness and safety for the treatment of patients with COPD. Methods: Eight databases will be systematically retrieved from their inceptions to February 2021. Inclusion criteria are randomized control trials of AA combined with routine western medicine interventions in the treatment of COPD at stable stage. The primary outcomes we focus on comprise clinical effective rate, TCM symptom score, quality of life, dyspnea, exercise capacity, lung function, frequency of acute exacerbation, adverse events. The research screening, data extraction, and risk of bias assessment will be conducted by 2 individuals independently, and divergence will be adjudicated by a third senior investigator. The Stata 13.1 software will be used for meta-analysis. The confidence of evidence will be classified adopting grading of recommendations assessment, development and evaluation (GRADE) algorithm and methodological quality of this SR will be assessed using assessment of multiple systematic reviews-2 (AMSTAR-2) tool. Results: This SR will provide evidence-based medical proof for the treatment of COPD at stable stage by AA combined with conventional western medicine interventions. The findings of this SR will be presented at relevant conferences and submitted for peer-review publication. Conclusions: The findings of this SR will provide up-todated summary proof for evaluating the effectiveness and safety of AA for COPD. Registration number: INPLASY 202140080.